2021
DOI: 10.1007/s00268-021-06261-7
|View full text |Cite
|
Sign up to set email alerts
|

Selecting the Next Generation of Surgeons: General Surgery Program Directors and Coordinators Perspective on USMLE Changes and Holistic Approach

Abstract: Introduction The United States Medical Licensing Examination (USMLE) was designed as a universal assessment tool for states to determine physician’s medical licensure's candidacy. Recent changes in the USMLE exam have changed the way future surgical residency candidate applications will be reviewed. The survey aimed to assess the effect of changes in USMLE exams—USMLE Step 1 pass/fail, complete dissolution of USMLE clinical skills exam, and the role of holistic review in future surgical residency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Preference signaling was implemented in OHNS 5 with the goals of mitigating a surge in applications, 1 aligning program and applicant interests during the interview selection phase, and enhancing the capacity for holistic review, the preferred method for candidate assessment. 6,7 While preference signaling has not previously been used in the residency application process, this system was developed and implemented in the economics PhD marketplace 8 and several authors [9][10][11][12] have advocated for this approach during the residency selection process.…”
Section: Introductionmentioning
confidence: 99%
“…Preference signaling was implemented in OHNS 5 with the goals of mitigating a surge in applications, 1 aligning program and applicant interests during the interview selection phase, and enhancing the capacity for holistic review, the preferred method for candidate assessment. 6,7 While preference signaling has not previously been used in the residency application process, this system was developed and implemented in the economics PhD marketplace 8 and several authors [9][10][11][12] have advocated for this approach during the residency selection process.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that some PDs will consider research of equal or greater importance than the Step 2 score is provocative. The changing significance of Step 2 is a topic that has been hotly debated of late, with multiple survey studies reporting and blog posts opining that PDs will consider Step 2 “the new Step 1.” 46–57 The sentiment that Step 2 will be relied on more heavily, at least compared with student research activity, was not expressed by respondents in this study. Most likely, the process of selecting applicants for interviews and ranking without a numeric Step 1 score will take several years to refine, and the question of whether research continues to be of equal or greater importance to the Step 2 score will merit revisiting at a future date.…”
Section: Discussionmentioning
confidence: 75%
“…A study performed by Aziz et al in 2021 determined the attitudes of general surgery program directors in regards to USMLE step 1 changing to pass/fail scoring. They concluded that not only will step 2CK scores become more emphasized, but that the medical school name, personal contacts, and clinical performance will hold more significance as well [ 25 ]. Program directors in the fields of otolaryngology, neurological surgery, plastic surgery, and orthopedic surgery also disagreed with the policy change based on studies from their respective specialty groups.…”
Section: Discussionmentioning
confidence: 99%